(3SjQ GdSda GdUGdMjf hGdCFeI GdegOjjfs - (3ESeGYjd Hf eMeO Hf GdaVd Hf Ydj GdbQTj CHh GdbGSe GdWdjMj GdJejej, bhGe GdSfI,J (B535 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eMji GdCehGJ hSGeY GdCUhGJ hebOQ GdCbhGJ s
(3hLeY GdeDda ajg CNHGQ GdUMGHg hGdJGHYjf hGdUhajI hGdYGQajfs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B323 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B293s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B342 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B84 s
Keywords: (3GdJGQjNs